Suicidal thoughts and behaviors associated with fluoroquinolone antibiotics: a real-world pharmacovigilance analysis - Yang, Lijuan; Chen, Congqin; Ding, Lingqing; Lu, Tingting; Li, Xiwen; Xiao, Jie (Frontiers in Pharmacology, 2025)
ObjectiveThis study aimed to systematically and scientifically investigate the potential associations between the use of fluoroquinolone antibiotics (ciprofloxacin, levofloxacin, moxifloxacin, ofloxacin, norfloxacin, and delafloxacin) and suicidal thoughts and behaviors using data from the Food and Drug Administration Adverse Event Reporting System (FAERS) database.MethodsThe FAERS database was queried from the first quarter of 2004 to the fourth quarter of 2023. Disproportionality analysis was conducted using the reporting odds ratio (ROR) and empirical Bayes geometric mean (EBGM).ResultsA total of 737 cases of suicidal thoughts and behaviors associated with fluoroquinolones (FQs) were reported in the FAERS database during the study period. Overall, FQs did not demonstrate a disproportionate increase in overall cases of suicidal thoughts and behaviors (ROR: 0.74, 95% CI: 0.69–0.79, P < 0.001; EBGM05: 0.69). Stratified analyses revealed no safety signals for suicidal thoughts and behaviors associated with FQs in either females or males. However, subgroup analyses by age groups demonstrated slightly elevated RORs for suicidal thoughts and behaviors in the <18 years age group (ROR: 1.51, 95% CI: 1.05–2.19, P = 0.03) and the 18–24 years age group (ROR: 2.31, 95% CI: 1.75–3.06, P < 0.001), although the EBGM05s values remained below two in both populations. No significant safety signals were observed in the other age groups.ConclusionThe analysis of reported cases of suicidal thoughts and behaviors in the FAERS database does not indicate an overall safety signal associated with fluoroquinolones (FQs) at present. Subgroup analysis revealed a slight increase in the RORs for suicidal thoughts and behaviors in the <18 years and the 18–24 years age group; however, no significant safety signal was detected based on the EBGM05s in these populations. Further comprehensive and prospective studies are necessary to confirm and validate these findings.